Optimizing an immunomodulatory potency assay for Mesenchymal Stromal Cell - Hansen, Stine Bangsgaard; Højgaard, Lisbeth Drozd; Kastrup, Jens; Ekblond, Annette; Follin, Bjarke; Juhl, Morten (Frontiers in Immunology, 2022)
The expeditious progress of mesenchymal stromal cells (MSC) for therapeutic intervention calls for means to compare differences in potency of cell products. The differences may be attributed to innumerable sources including tissue origin, production methods, or even between batches. While the immunomodulatory potential of MSC is recognized and well-documented by an expansive body of evidence, the methodologies and findings vary markedly. In this study, we utilized flowcytometric analysis of lymphocyte proliferation based on cryopreserved peripheral blood mononuclear cells for quantification of the inhibitory effect of MSC. Technical aspects of fluorescent staining and cryopreservation of peripheral blood mononuclear cells were evaluated to obtain optimal results and increase feasibility. A range of common specific and unspecific mitogens was titrated to identify the conditions, in which the effects of Adipose tissue-derived Stromal Cells (ASC; a type of MSC) were most pronounced. Specific stimulation by antibody-mediated activation of CD3 and CD28 via TransAct and Dynabeads lead to substantial proliferation of lymphocytes, which was inhibited by ASC. These results were closely mirrored when applying unspecific stimulation in form of phytohemagglutinin, but not concanavalin A or pokeweed mitogen. The mixed lymphocyte reaction is a common assay which exploits alloreactivity between donors. While arguably more physiologic, the output of the assay often varies substantially, and the extent of proliferation is limited since the frequency of alloreactive cells is low, as opposed to the mitogens. To heighten the proliferative response and robustness, combinations of 2-5 donors were tested. Maximum proliferation was observed when combining 4 or more donors, which was efficiently suppressed by ASC. Several desirable and unfavorable traits can be attributed to the tested stimuli in the form of keywords. The importance of these traits should be scored on a laboratory-level to identify the ideal mitogen. In our case the ranking listed PHA as the most suited candidate. Developing robust assays is no trivial feat. By disclosing the full methodological framework in the present study, we hope to aid others in establishing functional metrics on the road to potency assays.